AYRIM OG‘IR METALLARNING ATROF MUHITGA TA’SIRI - Kurbonov Sh.X (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2024)
In this article, the impact of heavy metals on the environment, a formal project on reducing the activity of heavy metals in the soil has been studied and developed.